Pathogenicity of Bacillus thuringiensis Berliner on Larvae and Adults of Blow Fly Chrysomya albiceps (Wiedemann,1819) (Diptera : Calliphoridae) - S. Mehdi, Nawal; S. Noshee, Zahraa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted to evaluate serial concentrations of commercial formulation suspension (Antrol) of Bacillus thuringiensis israelensis. As a microbial control agent against Chrysomya albiceps (blow fly) larvae and adults under laboratory conditions. The results revealed that percentages of accumulated mortalities of second instar larvae were 30 - 63.33% for the doses 100 – 2000 ppm respectively , Mortalities rate increased with increased of time, treating larval food with 1000 ppm of bacterial suspension caused mortality rate reached 30% after two days, later reached 72.96% after 12 days. The bio assays results of treating adults food showed that mortalities percentage were 6.67 – 73.33 when their food was treated by 100 – 2000 ppm of bacterial suspension. The results indicated that B. thuringiensis has a potential to be a bio control agent for Ch. albiceps.